(untitled) (Conferencea, 2022)
The article presents the results of a mathematical model of the deceleration of the car in the case of the first throat braking on the section under the influence of wind resistance. For the first time, analytical formulas were obtained to determine the braking distance and distance of the car in the first braking position. A timeline of the braking distance and distance of the car is plotted. According to the graphical analysis, the deceleration of the car in the case of the first brake depends mainly on the resistance of the car to the deceleration of the car on the section.